ExoventQ: A Novel Low-Cost Portable Negative Pressure Ventilator Design and Implementation - Shahd Sameer Mohammed Gaben (14152416) (2024)
The emergence of COVID-19 resulted in significant shortages of mechanical ventilators globally. This prompted investigations into developing new, cost-effective methods for producing ventilators. Different types of ventilators, such as positive pressure ventilators (PPVs), conventional negative pressure ventilators (NPVs), and biphasic cuirass ventilators (BCVs), were considered. However, PPVs were found to pose health risks and were expensive to manufacture. Thus, this study introduces ExoventQ, an innovative respiratory support device inspired by traditional NPV designs. ExoventQ was meticulously designed, simulated, implemented, and tested in two modes: continuous negative extrathoracic pressure (CNEP) and cyclic negative pressure ventilation (CNPV). It consists of three main components: a pressure vessel, a pumping system, and a control panel. Each component was designed with attention to pressure distribution, material, safety, cost, and portability. Through ANSYS stress analysis, ExoventQ was developed with a squircle-shaped polycarbonate vessel capable of withstanding up to 50 millibar (mbar) of vacuum pressure. This design also prevents airway tilting when placed on its side, providing more comfort for the patient. Pressure regulation inside the vessel is achieved through a bypass butterfly valve controlled by a servo motor. The user interface is implemented on a Raspberry Pi touchscreen, enabling input through rotating knobs and displaying output for monitoring. Safety measures include audio and visual alarms, along with a power switch that halts ventilation if the vacuum in the vessel drops below 40 mbar. The successful design and implementation of ExoventQ have the potential to enable mass production of safe and affordable NPVs to address pulmonary complications. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2024.3390566